THE NEED TO IMPROVE THE COMPETITIVE ENVIRONMENT WITH THE HELP OF TAXES (Academicia Globe: Inderscience Research, 2023)
Taxes play a major role in forming the competitiveness of business entities and ensuring equal conditions. First, taxes can be used as a tool to encourage desired business behavior and discourage anti-competitive practices. By implementing tax policies that encourage innovation, research and development, and investment in key industries, governments can foster a more competitive business environment. In addition, tax measures should be introduced to prevent monopolistic behavior, promote fair competition and prevent market distortions. Second, a transparent and predictable tax regime is essential to strengthen the competitive environment. Businesses thrive when they have confidence in their tax obligations and can plan effectively. Simplifying tax legislation, reducing administrative burdens, and providing clear guidelines and deadlines for tax compliance can significantly contribute to creating a competitive business environment. Third, promoting tax compliance and combating tax evasion is important to create a level playing field for business entities. When businesses engage in aggressive tax planning or tax evasion, this distorts competition and puts compliant businesses at a disadvantage. Implementing tax administration, including effective audit and enforcement mechanisms, ensures fair tax competition and helps maintain the integrity of the tax system.